Pole vault at the World Championships in athleteics - Helsinki 2005 - Schade, F.; Brüggemann, G. P.; Isolehto, J.; Komi, P. V.; Arampatzis, A. (2005)
The purpose of the pole vault project at the World Championships in Athletics in Helsinki is to provide biomechanical data of elite level pole vaulters and to improve the pole vault specific biomechanical knowledge as far as elite vaulting is concerned. This report focuses on: 1. approach velocity 2. forces exerted at the end of the pole in the planting box during the vault 3. mechanical energy parameters of the athlete and angular momentum during the vault. Topic 1 presents approach velocity data of the world`s best. Topic 2 contains examples of the reaction forces in the planting box during the vault of selected vaults. And Topic 3 contains a comparison of the male and female finalists and the decathletes on the basis of energy considerations and angular momentum.